2023
DOI: 10.3390/ijms24044187
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Diverse Roles of Neglected Genes Containing Domains of Unknown Function (DUFs): Progress and Perspective

Abstract: Domain of unknown function (DUF) is a general term for many uncharacterized domains with two distinct features: relatively conservative amino acid sequence and unknown function of the domain. In the Pfam 35.0 database, 4795 (24%) gene families belong to the DUF type, yet, their functions remain to be explored. This review summarizes the characteristics of the DUF protein families and their functions in regulating plant growth and development, generating responses to biotic and abiotic stress, and other regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Among 126 F2 populations, no recombination was found in the corresponding locus of CmoCh14G005820 gene, so this gene was predicted to be a candidate gene conferring white-flower phenotype in pumpkin. and plant response to abiotic stress (Gu & Cheng, 2014;Lv et al, 2023;Qin et al, 2013;Zhou et al, 2020). Gene annotation showed that CmoCh14G005820 encoded a CmoDUF1997 protein in pumpkin, but the relationship between this protein and flower-colour formation was not characterised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 126 F2 populations, no recombination was found in the corresponding locus of CmoCh14G005820 gene, so this gene was predicted to be a candidate gene conferring white-flower phenotype in pumpkin. and plant response to abiotic stress (Gu & Cheng, 2014;Lv et al, 2023;Qin et al, 2013;Zhou et al, 2020). Gene annotation showed that CmoCh14G005820 encoded a CmoDUF1997 protein in pumpkin, but the relationship between this protein and flower-colour formation was not characterised.…”
Section: Discussionmentioning
confidence: 99%
“…They contain at least one highly conserved DUF domain in their protein structure. Studies have shown that DUF genes play an important role in regulating the wall development of plant cells, plant growth and development, flower and fruit development, plant defence response to pests and diseases and plant response to abiotic stress (Gu & Cheng, 2014; Lv et al, 2023; Qin et al, 2013; Zhou et al, 2020). Gene annotation showed that CmoCh14G005820 encoded a CmoDUF1997 protein in pumpkin, but the relationship between this protein and flower‐colour formation was not characterised.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins sharing the same DUF are classified into distinct DUF families [ 22 ]. The DUF protein family plays a pivotal role in the regulation of plant growth and development, mediating responses to both biotic and abiotic stresses, as well as fulfilling various regulatory functions throughout the life cycle of plants [ 24 ]. The following protein domains have undergone functional characterization in Arabidopsis thaliana : DUF6 [ 25 ], DUF26 [ 26 ], DUF246 [ 27 ], DUF538 [ 28 ], DUF579 [ 29 ], DUF617 [ 30 ], DUF642 [ 31 ], DUF647 [ 32 ], DUF724 [ 33 ], DUF784 [ 34 ], DUF1117 [ 35 ], DUF1218 [ 36 ], DUF4005 [ 37 ] and DUF4228 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The domains of unknown function (DUF) family refers to a series of protein families whose functions have not yet been annotated [ 6 ]. Currently, the Pfam database (V35.0) contains 4795 DUF families, accounting for 24% of all Pfam families [ 7 ]. Studies showed that different DUF proteins have a variety of functions.…”
Section: Introductionmentioning
confidence: 99%